2010
DOI: 10.1111/j.1445-2197.2009.05204.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of imaging of scaphoid fractures

Abstract: Scaphoid fractures are the most common fractures of the carpus, accounting for 79% of all carpal fractures. Early diagnosis of scaphoid fractures is imperative owing to potential complications following the fracture, including non-union, avascular necrosis, carpal instability and osteoarthritis. Plain radiography remains the initial imaging modality to assess scaphoid fractures. Magnetic resonance imaging (MRI) is excellent in the detection of clinically suspected, but initially radiographically negative, scap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 73 publications
(165 reference statements)
1
26
0
3
Order By: Relevance
“…If a fracture is suspected, MRI is considered inferior to CT for the identification of fracture location, morphology, displacement and union status 8. Smith et al therefore recommend CT as standard after all initial positive radiographs 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a fracture is suspected, MRI is considered inferior to CT for the identification of fracture location, morphology, displacement and union status 8. Smith et al therefore recommend CT as standard after all initial positive radiographs 8.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al therefore recommend CT as standard after all initial positive radiographs 8. CT also has an 85.2% sensitivity and 99.5% specificity for the detection of acute scaphoid fracture 15.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in a study, an 11-yearold with multiple undisplaced carpal fractures was treated conservatively and achieved adequate fracture healing. 9 Further magnetic resonance imaging may aid diagnosis and reveal displacement of carpal fractures in children, [9][10][11] as radiographs fail to reveal fractures in 37% of children with hand or wrist injuries. 12 A high level of suspicion is therefore important in children with hand or wrist injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Dias et al also reported that radiographs taken 12 weeks after a scaphoid fracture do not provide reliable and reproducible evidence of healing [1]. Many authors have reported that computerized tomography is the preferred method of assessing scaphoid fracture location, deformity, displacement, and union status [2,10-14], and it was also reported by Bain that computerized tomography (CT) scans have a higher correlation with operative findings [14]. …”
Section: Introductionmentioning
confidence: 99%